The Application of Virtual Reality Technology in Education: Transforming Learning Experiences - Ibroximxonova Diyora Jamshid kizi (Euro Asian Journal Publishing, 2024)
Virtual Reality (VR) technology has emerged as a transformative tool in various sectors, with education being one of the most promising areas of application. This paper discusses the benefits, challenges, and future possible directions of using virtual reality in education settings. We demonstrate how VR can be used to increase students' engagement, enhance retention, and provide immersive learning experiences through case studies and existing applications scenarios.
Keywords: Virtual Reality; Immersive Learning; 3D Simulation